2021
DOI: 10.3390/molecules26175136
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Reactive Oxygen Species Generation and Aneuploidy Induction Contribute to Thymoquinone Anticancer Activity

Abstract: Thymoquinone (TQ) is the main biologically active constituent of Nigella sativa. Many studies have confirmed its anticancer actions. Herein, we investigated the different anticancer activities of, and considered resistance mechanisms to, TQ. MTT and clonogenic data showed TQ’s ability to suppress breast MDA-MB-468 and T-47D proliferation at lower concentrations compared to other cancer and non-transformed cell lines tested (GI50 values ≤ 1.5 µM). Flow-cytometric analyses revealed that TQ consistently induced M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
(45 reference statements)
2
12
0
Order By: Relevance
“…A notable, two-fold increase in ROS was observed in cells that were treated with 7.5 μM thymoquinone for 5hr ( Fig 8A and 8B ). Whereas GSH is known to control ROS production and is implicated in thymoquinone resistance [ 34 ], recent findings indicate that sulfur/cysteine sequestration is a rate limiting variable to initiate development during starvation [ 33 ]. Moreover, because GSH is an essential to the conjugation of multiple substrates in GST enzyme activity, we measured the levels of oxidized and reduced glutathione (GSSG, GSH).…”
Section: Resultsmentioning
confidence: 99%
“…A notable, two-fold increase in ROS was observed in cells that were treated with 7.5 μM thymoquinone for 5hr ( Fig 8A and 8B ). Whereas GSH is known to control ROS production and is implicated in thymoquinone resistance [ 34 ], recent findings indicate that sulfur/cysteine sequestration is a rate limiting variable to initiate development during starvation [ 33 ]. Moreover, because GSH is an essential to the conjugation of multiple substrates in GST enzyme activity, we measured the levels of oxidized and reduced glutathione (GSSG, GSH).…”
Section: Resultsmentioning
confidence: 99%
“…28,42,43 Furthermore, TQ induced apoptosis in cancer cells by promoting glucose oxidative phosphorylation following inhibition of LDHA enzyme, enhancing ROS production with declines in antioxidants, and downregulating the PI3K/mTOR/HIF1α network. [24][25][26][27][28][29] Further studies have also reported that combining 5-FU with TQ 28,32 or Met 23,33 resulted in boosted in vitro and in vivo anti-cancer actions against CRC. Although more recent reports have also shown enhanced anti-cancer effects for TQ and Met co-therapy in human leukemic cell lines 30 and breast cancer in mice, 31 there is no report regarding their combination against CRC.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23] Similarly, the main active compound of the black seed, thymoquinone (TQ), has demonstrated efficient tumoricidal actions against CRC by inhibiting the PI3K/mTOR/HIF1α network, inducing oxidative glycolysis, and increasing oxidative stressmediated apoptosis. [24][25][26][27][28][29] Moreover, others have reported boosted anti-cancer effects against leukemia and breast cancer following co-treatment with metformin and TQ, 30,31 as well as by adding each of them with 5-FU for the treatment of CRC. 23,28,32,33 However, none of the prior reports investigated the potential beneficial effects of combining metformin and TQ, with and without 5-FU, against colon neoplasia.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of thymoquinone (a key component of Nigella sativa —black cumin seed—oil) and of pyrroloquinoline quinone (PQQ)—a vitamin-like compound in the diet that binds with high affinity to lactate dehydrogenase—to boost Sirt1 activity rests in their ability to promote oxidation of NADH to NAD+. The antioxidant enzyme NAD(P)H quinone oxidoreductase 1 (NQO1) can reduce thymoquinone to thymohydroquinone, converting NADH to NAD+ in the process; thymohydroquinone can then act as a scavenging antioxidant [ 160 ]. This mechanism can explain thymoquinone’s ability to activated Sirt1 [ 161 , 162 , 163 ].…”
Section: Nutraceuticals For Promoting Mitophagy and Mitochondrial Bio...mentioning
confidence: 99%